Utility of the Right to Health for Addressing Skilled Health Worker Shortages in Low- and Middle-Income Countries - Kenneth Yakubu; Seye Abimbola; Andrea Durbach; Christine Balane; David Peiris; Rohina Joshi (Kerman University of Medical Sciences, 2022)
Background  As a fundamental human right, the right to health (RTH) can influence state actors' behaviour towards health inequities. Human rights advocates have invoked the RTH in a collective demand for improved access to essential medicines in low- and middle-income countries (LMICs). Similarly, scholars have used the RTH as a framework for analysing health problems. However, its utility for addressing skilled health worker (SHW) shortages in LMICs has been understudied. Realising that SHW shortages occur due to existing push-and-pull factors within and between LMICs and high-income countries (HICs), we sought to answer the question: "how, why, and under what circumstance does the RTH offer utility for addressing SHW shortages in LMICs?"Methods  We conducted a realist synthesis of evidence identified through a systematic search of peer-reviewed articles in Embase, Global Health, Medline (Ovid), ProQuest - Health & Medical databases, Scopus (Elsevier), Web of Science (Clarivate), CINAHL (EBSCO), APAIS-Health, Health Systems Evidence and PDQ-EVIDENCE; as well as grey literature from Google Scholar.Results  We found that the RTH offers utility for addressing SHW shortages in LMICs through HIC state actors' concerns for their countries' reputational risk, recognition of their obligation to support health workforce strengthening in LMICs, and concerns for the cost implication. State actors in LMICs will respond to adopt programs inspired by the RTH when they are convinced that it offers tangible national benefits and are not overly burdened with ensuring its success. The socio-economic and institutional factors that constrain state actors' response include financial cost and sustainability of rights'-based options.Conclusion  State and non-state actors can use the RTH as a resource for promoting collective action towards addressing SHW shortages in LMICs. It can also inform negotiations between state actors in LMICs and their HIC counterparts.